Some Requirements of Post-War Forest Policy in the C.P - Maitland, V. K. (Indian Forester, 1944)
The note on Post-war Forest Policy was originally prepared by the Conservator of Forests, Eastern Circle, Central Provinces, as a letter to the ProvincialGovernment.It was felt that the views expressed by Mr. Maitland would be of interest to the readers of the "Indian Forester" and permission was obtained from the Government of the Central Provinces to publish the note with a few minor corrections.